2006
DOI: 10.1007/s00586-006-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Is a collagen scaffold for a tissue engineered nucleus replacement capable of restoring disc height and stability in an animal model?

Abstract: The idea of a tissue engineered nucleus implant is to seed cells in a three-dimensional collagen matrix. This matrix may serve as a scaffold for a tissue engineered nucleus implant. The aim of this study was to investigate whether implantation of the collagen matrix into a spinal segment after nucleotomy is able to restore disc height and flexibility. The implant basically consists of condensed collagen type-I matrix. For clinical use, this matrix will be used for reinforcing and supporting the culturing of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 28 publications
6
72
1
1
Order By: Relevance
“…Subcutaneous implantation was used and the implant was never exposed to physiological loading. Recently, there is one ex vivo study reporting collagen nucleus replacement in bovine discs under mechanical loading [121]. Although restoration of disc height is possible, extrusion of the whole implant after a few loading cycles have been reported.…”
Section: Scaffolding In Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous implantation was used and the implant was never exposed to physiological loading. Recently, there is one ex vivo study reporting collagen nucleus replacement in bovine discs under mechanical loading [121]. Although restoration of disc height is possible, extrusion of the whole implant after a few loading cycles have been reported.…”
Section: Scaffolding In Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…A wide range of biomaterials dominated by natural biomaterials has been used for nucleus replacement. These materials include collagen [121], atellocollagen [98,99], alginate [70,76], gelatin [118], chitosan [33], collagen/ glycosaminoglycan [97], collagen/hyaluronan [2] and poly-L-lactic acid [94]. Reviews for nucleus replacements have been reported elsewhere [29,103].…”
Section: Scaffolding In Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…Injected cells and fibrin matrix (without UVL polymerization) get lost easily through this annular lesion [3,4,6,7]. Consequently, the nucleus is exposed to the immune system and to detrimental degenerative cascades with upregulation of MMPs [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, at present such approaches to humans are still rare and limited due to remaining concerns about safety and biological potency. Although tremendous efforts have been made to improve disc cell therapy, today's results are rather disappointing with early loss of implanted cells caused by annular damage at the injection site and cell death due to the harsh intradiscal environment characterized by insufficient nutrition, accumulation of waste products and high intradiscal pressures [3][4][5][6][7]. Additionally, cell-based strategies are expensive, time demanding, and invasive with potentially more complications, since autologous cells have to be collected in a first operation, with the need for processing and cultivation, and then application to the disc in a second operative procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The three main components of IVD aimed at tissue regeneration are: 1) AF (Sato et al, 2003;Chang et al, 2007;Helen and Gough, 2007;Nerurkar et al, 2007;Shao and Hunter, 2007;Wan et al, 2007;Nerurkar et al, 2008;Wang et al, 2008;Nerurkar et al, 2009); 2) NP (Baer et al, 2001;Sakai et al, 2003;Seguin et al, 2004;Bertram et al, 2005;Wilke et al, 2006;Roughley et al, 2006;Cloyd et al, 2007;Chou et al, 2008;Halloran et al, 2008;Richardson et al, 2008;Vernengo et al, 2008;Bron et al, 2009;Chou et al, 2009;Sawamura et al, 2009;Calderon et al, 2010;Silva-Correia et al, 2010a;Silva-Correia et al, 2010b;Reza and Nicoll, 2010;); and 3) both NP and AF by means of using biphasic scaffolds (Mizuno et al, 2004;Hamilton et al, 2005;Mizuno et al, 2006;Nerurkar et al, 2008;Nesti et al, 2008). It has been proposed that for producing a tissue resembling natural IVD, total IVD replacement could be required.…”
Section: Polymeric-based Designsmentioning
confidence: 99%